2006
DOI: 10.1634/stemcells.2006-0687
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Receptor Expression in Non-Small Cell Lung Carcinoma: A Question of Antibody Specificity

Abstract: STEM CELLS 2007;25:718 -722

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 17 publications
3
62
0
Order By: Relevance
“…They concluded that Epo treatment might adversely affect the prognosis of head and neck cancer patients if cancer cells express EpoRs. We strongly agree with the reservations expressed by Della Ragione and colleagues [10] concerning the specificity of the EpoR C20 antibody used in this recent study by Henke et al [9] because it has been clearly demonstrated that it cross-reacts with heat shock protein-70 [11,12].…”
Section: In Reply Terence R J Lappin a Peter Maxwell Patrick G supporting
confidence: 91%
“…They concluded that Epo treatment might adversely affect the prognosis of head and neck cancer patients if cancer cells express EpoRs. We strongly agree with the reservations expressed by Della Ragione and colleagues [10] concerning the specificity of the EpoR C20 antibody used in this recent study by Henke et al [9] because it has been clearly demonstrated that it cross-reacts with heat shock protein-70 [11,12].…”
Section: In Reply Terence R J Lappin a Peter Maxwell Patrick G supporting
confidence: 91%
“…In addition, currently available EPO receptor antibodies lack specificity and generally identify heat shock protein (hsp)70, a poor prognosis tumor marker [28]. Although a recent study suggested that preabsorption of the currently used EPO receptor antiserum C20 with an hsp70 peptide improved antibody specificity for plasma membrane-associated protein, the study was done using NSCLC tissue microarrays, only 30% of the tumors retained membrane staining, and no control tissue was studied to confirm antibody specificity for the EPO receptor in this system [29]. Reports using such antibodies to demonstrate EPO receptor expression in tumor cells by immunohistochemistry or immunoblotting should, therefore, be viewed with caution.…”
Section: Tumor Progression Resulting From Stimulation Of Tumor Cell Ementioning
confidence: 99%
“…We used the polyclonal antibody (M-20) previously shown to have a reliable specificity (Lopez et al 2011) to identify the EpoR by Western blot and immunohistochemistry, since the anti-EpoR antibody (C-20 Santa Cruz Biotech) has been reported to cross-react with HSP70, which is also highly expressed in tumor tissue (Brown et al 2007). Interestingly, the detection of an approximately 59 kDa band by Western blot using the polyclonal M-20 antibody suggested the significantly overexpressed presence of the EpoR in liver tissue during CC development, as also confirmed by RT-PCR analysis.…”
Section: Discussionmentioning
confidence: 99%